Challenges and Strategies of Physical Education Teachers in Multicultural Elementary Schools - Ilyasa Laudza; Cahyo Yuwono (Journal of Physical Education Health and Sport, 2026)
The increasing cultural diversity in primary schools presents significant pedagogical challenges for physical education (PE) teachers. This study examines the difficulties experienced by PE teachers when working in multicultural learning environments and explores the strategies they employ to promote inclusive participation. Using a qualitative approach, data were collected through interviews and classroom observations involving two primary school PE teachers in culturally diverse. The data were analyzed using thematic analysis to identify recurring pattern and key themes. The findings indicate that language differences, varying cultural norms related to physical activity, and differing levels of prior sport experience influence classroom interaction and student engagement. Teachers responded to these challenges by adapting instructional methods, modifying activities, implementing cooperative learning models, and fostering culturally responsive communication. The study highlights the importance of intercultural competence and reflective teaching practices in creating equitable PE environments. These findings suggest that professional development programs should prioritize inclusive pedagogical strategies to better prepare teachers for multicultural classrooms.